Zoneamento ambiental em bacias hidrográficas. Estudo de caso: zoneamento ambiental da microbacia hidrográfica das nascentes do rio Ibicui Mirim até a barragem Saturnino de Brito - Daltrozo, Cleonir Carpes (2008)
The Environment Zoning is a legal instrument of ordinance of the use and occupation of the ground. The main goal of this work is classify the allowed, not allowed, conflicting territory in use zones, activities, in accordance with the capacity of support of ecosystems and the economic interest. The Environment Zoning of the Hydrographic Basin of the Ibicuí-Mirim River until the Saturnino de Brito dam allowed to evaluate existing Environment deterioration in the related basin. For the accomplishment of the analyses that had allowed the elaboration of the environmental zoning map had been evaluated ten (10) parameters: declivity, drainage, density, ruggedness number, vegetation, wild life, native landscape, human occupation, land use, erosion, propitious areas forest fires or burnt areas. With the attainment of estimated values of each one of the ten (10) analyzed parameters and with the aid of the equation deduced for these parameters, the percentage of deterioration of each one of the evaluated environment units was gotten. After this, in accordance with the proposed methodology was considered six (6) distinct types of zoning classes in the related basin: Permanent Preservation Area (APP), subdivided in: Zone Zero and Zone 1; Conservation Permanent Area (the ACP), subdivided in: Zone 2 and Zone 3; Restoration Area (AR), Zone 4 and Occupation Area (AUO) Zone 5, with its aptitudes and restrictions. With the attainment of the respective areas for each class of the territory ordinance was elaborated the environment zoning chart of the Hydrographic Basin considered and was done the respective recommendations in accordance with its aptitudes, also the suggestion of the creation of an APA (Environment Protection Area) with the elaboration of the respective Law Decree.